Photoinduced absorption and nonlinear optics of triglycine selenate single crystals under uniaxial pressure - Ozga, K.; Ali Hussein, Reshak, Prof. Dr.; Berdowski, J.; Tylczyński, Z.; Wojciechowski, A.; Ślȩzak, A.; Kityk, I. V. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/